The impact of information and communication technologies on vocational competences and training : case studies in Italy, France and Spain. Synthesis report - Gatti, Mario [Verfasser]; Garcia Gonzalez, Lazaro [Verfasser]; Mereu, Maria Grazia [Verfasser]; Tagliaferro, Claudio [Verfasser] (Office for Official Publications of the European Communities, 2000)
This study is a consolidation of the findings acquired in the course of three parallel surveys conducted in France, Italy, and Spain on the impact of new technologies in the telecommunications and administration/office sectors. Data are from an ad hoc interview questionnaire directed at the people in charge of functional areas of the firm and managers of human resources and training. Chapters 2-5 focus on the following four factors that were analyzed in the interviews: the development of company strategies, organizational changes, and the criteria adopted in the choice of technological solutions; the influence of those changes on the competence of the typical practitioners identified in an earlier study; the trends in occupations and vocational competence; and the impact of technologies on vocational training. Chapter 6 makes recommendations on training and the development of skills in a context of technological change. It identifies these four basic skills for working in an information technology context: a sense of personal initiative and creativity; social skills and the ability to work as a team; organizational skills and a system-wide view of organizations; and fluidity in spoken and written language. The report also suggests a social plan to back plans for technological innovation, new content of continuing training, and innovative practices for organizations. (BIBB-Doku)
Keywords: G 2.2.1 Technologisierung; G 2.2 Informations- / Wissensgesellschaft; G 1.2.3 Qualifikationsentwicklungen; G 2.3.4 Qualifikationswandel; G 1.2.4.2.6 Öffentliche Verwaltung, Verteidigung, Sozialversicherung; I 2.2.1 Westeuropa; Informationstechnik; Informationstechnische Bildung; Berufliche Qualifikation; Qualifikationswandel; Telekommunikation; Verwaltung; Internationaler Vergleich; Frankreich; Italien; Spanien